Skills needed to communicate adequately COVID-19 risk indicators to citizens and policy-makers. (20th October 2021) - Greco, D
Abstract: Risk communication is a sustained communication process established with a diverse audience about the likelihood of the health outcomes of specific conditions or actions. Individuals are influenced by risk information in complex and unpredictable ways and communicating effectively risk during a pandemic event requires a set of different skills: 1) analysis skills, to be able to gather and assess the information; 2) communication skills, to deliver information that is understandable, through the right channels for the specific audience; 3) coordination and leadership skills, to be able to align partners at local, regional, national, international level to meet common goals. In this presentation, challenges of communicating COVID-19 risk indicators such as the risk of infection, risk of being hospitalised, risk of death, risk of long-term consequences, and risk of adverse events from vaccination will be presented. In particular, through case studies we will examine local, national and international risk communication strategies on: 1) risk of death in the vulnerable population; 2) risk of transmission in the home setting; 3) risk of long-term consequences of COVID-19 ("long COVID"). The strengths and weaknesses of the communication strategies in these examples will be pointed out and opportunities to improve them will be covered.